Contribution à l’étude de quelques souches d’actinomycètes productrices des amylases, et détermination de leurs paramètres cinétiques vis-à-vis de leur substrat spécifique - Zerrouki, mokhtaria; Bourada, hanane (My University, 2019)
Actinobacteria represent an important biological source in the production of enzymes that are applied in industries, such as the use of amylases in the biodegradation of starch. The main objective of our work is focused on the isolation and identification of four soil actinobactia strains in the region of Abd-El-Malak Ramdhan (Mostaganem).These strains will be selected and characterized by physiological and biochemical tests. The inocula of the four isolates were used in a starchy liquid medium for the production of amylase enzymes. After extraction, the enzymatic activity of the amylase extracts was evaluated by two methods of colorimetric assays of Biuret and Fehling Liqeur performed at wavelengths λ=540 nm. This evaluation focused on the quantification of enzymatic extracts of actinomycete strains, as well as the products released after substrate hydrolysis (starch). This last one makes it possible to determine the kinetic parameters of the raw amyliotic extracts Vmax, Km and Vi. The results obtained confirm that the four isolates of actinobacteria belong to the genus Streptomyces sp. The crude enzymatic extracts of the strains had protein concentrations (0.081, 0.101, 0.112 and 0.115 mol / l) respectively for the four isolates (S2, S5, S8 and S9). However, the Km values are very low, obtained respectively with the extracts of S2, S5 and S9 (12.5×10-3, 7×10-3, 10.5×10-3). Speeds are higher for the same strains (5.2×10-3, 12×10-3, 8.2×10-3 mol.l-1.min-1) compared to strain S8 (km= 6×10-3, Vi = 11×10-3 mol.l-1.min-1), which it is desirable to purify the amylase enzyme and monitor the growth of the three strains S2, S5 and S9 on optimized medium, for study well and determine their production mechanisms for the enzyme.
Keywords: Streptomyces sp; Amylase; Km constant; Initial speed Vi.